Invigoration of Katokkon chili (Capsicum chínense Jacq.) seeds using halopriming and duration of immersion. Issue 4 (July 2021) - Mantja, K; Dermawan, R; Nurfaida,; Iswoyo, H; Syaiful, S A; Dytheana, A
Abstract: A study was carried out to study the response of katokkon seeds to invigoration treatment using atonic substances, phosphoric acid, and KCl. This research was conducted in the form of an experiment using a randomized block design (RBD) 21. Invigoration treatments were given consisting of a combination of atonic substances, phosphoric acid and KCl with different immersion times. The results showed that the invigoration treatment package on the seeds that gave the best effect on the germination and vigor of the chili seeds was the best percentage value of sprouts, namely the package with atonic solution with a soaking time of 6 hours (75%), the percentage value of the vigor index, namely the package with long atonic solution immersion for 6 hours (95.00). Plumula length with a package consisting of a 6 hour immersion phosphoric acid solution with a plumule length (0.24 cm), a radicle length with a package consisting of 3 hours immersion atonic solution with a radicle length (0.51 cm), plant height with a package consisting of acidic solution Phosphate immersion 3 hours with high (9.49 cm), and long roots with a package consisting of a 12 hour long immersion atonic solution (14.02 cm).